Repellent effect of three plant extracts on pests of the crop of Capsicum chinense - Gio-Trujillo, José Alberto; José Luis (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of the study was to evaluate the repellent effect of ethanolic extracts from seeds of Azadirachta indica, Pachyrhizus erosus and leaves of Gliricidia sepium, on pests in Capsicum chinense, Var. magnum orange. A block design was used with three treatments (T1: A. indica, T2: P. erosus, T3: G. sepium) and a negative control with five repetitions per treatment (lot of 15 plants). For the extraction of the treatments, the method of maceration and infusion in ethanol-distilled water was used. The treatments were applied every 7 days, spraying 15 ml/L of water. Twelve daily samplings were carried out for counting and visual identification of pests. In total, the incidence of eight pest species was observed. Bemicia tabasi, Epitrix spp. and Liriomyza spp. predominated in the crop. The ethanolic extract of G. sepium registered the lowest incidence of pests such as B. tabasi and Empoasca spp (p< 0.05).